PENGARUH TINGKAT KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH BANK PERKREDITAN RAKYAT LOGO KARO ASRI BERASTAGI - Menanti Sembiring; Salsalina Br Karo (JURNAL AGRICA, 2018)
This research  aimed  to know the influence  of  satisfaction and trust to the  customer loyality in  PT Bank Perkreditan Rakyat Logo Karo Asri Berastagi.   Population of this research is about 1881Bof people and to be taken about 95 of people to become sample.Technique of collecting data which is used is by questioner that by doing sharing questioner to respondent. Technique of analyzing data which is used is Multiple Linier Regression. The result of this research showed that partially, satisfaction and trust influence to the customer loyality in PT. Bank Perkreditan Rakyat Logo Karo Asri Berastagi. Simultaneously,satisfaction and trust also to the customer loyality in PT. Bank Perkreditan Logo Karo Asri Berastagi.Adjusted R Squere amount to 0,500 which mean  50 %  customer loyality in PT. Bank Perkreditan Rakyat Logo Karo Asri Berastagi was influence by satisfaction and trust while the residual 50% was influence by the other factors. Keywords : Satisfaction,trust, loyality